How Much Is Too Much? Intrapartum Interventions in a Term Singleton US Birth Cohort [19N]. (May 2020) - Nethery, Elizabeth; Painter, Ian; Sitcov, Kristin; Souter, Vivienne
Abstract : INTRODUCTION: Ideal rates of intrapartum interventions are unknown. Contemporary data from the US on the prevalence of these interventions is limited. The aim of this study was to evaluate rates of intervention in term singleton pregnancies. METHODS: This study uses a retrospective cohort of births at 17 hospitals in the Northwest US between 04/01/2017 and 03/31/2019. We report mode of delivery (cesarean with no labor/cesarean following labor/vaginal) and labor onset (spontaneous/induced). For spontaneous labors, we report rates of artificial rupture of the membranes (in those with intact membranes at admission), oxytocin augmentation, operative delivery, anesthesia (regional or general) and episiotomy. The proportion of pregnancies subject to none of these interventions was also evaluated. RESULTS: Of 47, 770 singleton term pregnancies in this cohort, 8, 485 (17.8%) had a cesarean without labor and 13, 857 (29.0%) underwent induction of labor. Spontaneous labor occurred in 25, 428 (53.2%) of all singleton term births. Interventions in spontaneous labor included: artificial rupture of the membranes in 63.9% (10, 509/16, 454) with intact membranes at admission, oxytocin augmentation in 9, 227 (36.3%), cesarean birth in 2, 594 (10.2%), operative vaginal birth in 1, 250 (5.8%), anesthesia in 16, 458 (64.7%) and episiotomy in 594 (2.3%). Only 4.6% (2, 229) of all singleton term births followed spontaneous labor without any of the interventions evaluated. CONCLUSION: Intervention is common in this population and only 1 in 20 singleton term births occurred without any of the evaluated interventions. More research is needed into the effectiveness of obstetric interventions, particularly in spontaneous term labor.